The Long Run Relationship Between Stock Indices and Macroeconomic Variables - Yogesh Maheshwari; KT Vigneswara Rao (The International Journal of Banking and Finance, 2015)
Stock indices are considered to be the barometers of any economy. This study examines the long run equilibrium relationship between stock indices and macroeconomic variables by applying the Johansen and Juselius (1990) Vector Error Correction Framework. It considers sector indices of the Bombay Stock Exchange and select macroeconomic variables for this purpose. The empirical results reveal that the stock indices and the macroeconomic variables are cointegrated and possess a longrun equilibrium relationship. The relationship has been found to be significantly negative with the index of industrial production, rupee-dollar exchange rate, foreign exchange reserves and wholesale price index, but significantly positive with money supply. The results of the study would enable investors and traders in taking informed decisions. They would also help companies in developing a view on the economy so as to facilitate their financial planning process.